Moving toward the ugly: A politic beyond desirability - Mingus, Mia (Leaving Evidence, 2011)
*Femmes Of Color Symposium Keynote Speech, Oakland, CA (8/21/11)
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3100; identités LGBTQIA2+; premier cycle; privilèges; queer; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppressions; thématiques

“Disability Justice” is simply another term for love - Mingus, Mia (Leaving Evidence, 2018)
This was the opening keynote speech at the 2018 Disability Intersectionality Summit, in Cambridge, Massachusetts on Oct 13, 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capacitisme; corps; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; militance; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis